2019
DOI: 10.1055/s-0039-1690620
|View full text |Cite
|
Sign up to set email alerts
|

A Metathetic Approach to [5/5/6] Aza-Tricyclic Core of Dendrobine, Kopsanone, and Lycopalhine A Type of Alkaloids

Abstract: A concise synthetic approach to [5/5/6] tricyclic pyrrolidine core of dendrobine is reported. This methodology relies on the construction of β-hydroxylactams by NaBH4-I2 reduction followed by reaction of allylsilane with the aid of Lewis acid to generate alkenyl lactams in good yields. Further, ring-opening metathesis (ROM) followed by ring-closing metathesis (RCM) were used to assemble the [5/5/6] aza-tricyclic skeleton of dendrobine. This short synthetic route has been expanded to assemble tricyclic [5/5/8] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…However, it was found that the pure trans -isomers 6aA , 6eA and 6pA are able to form tricyclic systems of cyclopenta[ b ]furo[2,3- c ]pyrrole 7 in the RRM reaction (the last column of Table 2 and Table 4 ). Moreover, in contrast to the communications [ 9 , 10 , 11 , 17 , 19 , 21 , 22 ], in our case, the ring-rearrangement metathesis does not require the supporting application of ethylene that facilitates practical synthesis.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…However, it was found that the pure trans -isomers 6aA , 6eA and 6pA are able to form tricyclic systems of cyclopenta[ b ]furo[2,3- c ]pyrrole 7 in the RRM reaction (the last column of Table 2 and Table 4 ). Moreover, in contrast to the communications [ 9 , 10 , 11 , 17 , 19 , 21 , 22 ], in our case, the ring-rearrangement metathesis does not require the supporting application of ethylene that facilitates practical synthesis.…”
Section: Resultsmentioning
confidence: 88%
“…It worth mentioning here that by revising the ethylene-supported transformations of the similar substrates [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], the question of the sequence of metathesis stages arose. In theory, two paths exist for the rearrangement of 6 to 7 in an ethylene atmosphere: ROM/RCM, or vice versa, RCM/ROM successions [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Allylation [11a] of 7 with allyltrimethyl silane in the presence of Lewis‐acid such as BF 3 .OEt 2 at 0 °C furnished the allyl derivative 8 . The stereochemistry of the newly introduced allyl group in 8 is established based on our earlier reported results [11b] . Unfortunately, the treatment of the allyl derivative 8 with G‐II catalyst did not deliver the ring‐rearranged product 10 , however, ring‐opening metathesis product 9 was observed in the presence of Hoyeda ‐Grubbs’ first‐generation (GH‐I) catalyst in 72 % yield.…”
Section: Resultsmentioning
confidence: 97%